Metformin transiently inhibits colorectal cancer cell proliferation as a result of either AMPK activation or increased ROS production. Issue 1 (December 2017) - Mogavero, Angela; Maiorana, Maria; Zanutto, Susanna; Varinelli, Luca; Bozzi, Fabio; Belfiore, Antonino; Volpi, Chiara; Gloghini, Annunziata; Pierotti, Marco; Gariboldi, Manuela
Abstract Metformin is a widely used and well-tolerated anti-diabetic drug that can reduce cancer risk and improve the prognosis of certain malignancies. However, the mechanism underlying its anti-cancer effect is still unclear. We studied the anti-cancer activity of metformin on colorectal cancer (CRC) by using the drug to treat HT29, HCT116 and HCT116 p53−/− CRC cells. Metformin reduced cell proliferation and migration by inducing cell cycle arrest in the G0/G1 phase. This was accompanied by a sharp decrease in the expression of c-Myc and down-regulation of IGF1R. The anti-proliferative action of metformin was mediated by two different mechanisms: AMPK activation and increase in the production of reactive oxygen species, which suppressed the mTOR pathway and its downstream targets S6 and 4EBP1. A reduction in CD44 and LGR5 expression suggested that the drug had an effect on tumour cells with stem characteristics. However, a colony formation assay showed that metformin slowed the cells' ability to form colonies without arresting cell growth, as confirmed by absence of apoptosis, autophagy or senescence. Our finding that metformin only transiently arrests CRC cell growth suggests that efforts should be made to identify compounds that combined with the biguanide can act synergistically to induce cell death.